Respuesta :

Answer:

3xy² -  14y²      

Step-by-step explanation:

I hope that this is the problem

   - x²y + [ - (x²y - 2xy² + y²) + (xy² - 3y² + x²y)] - (10y² - x²y)

= - x²y + [ - x²y + 2xy² - y² + xy² - 3y² + x²y] - 10y² + x²y

Now combine like terms in the [  ].

= - x²y  + [ -x²y + x²y + 2xy² + xy² - y² - 3y² ] - 10y² + x²y

= - x²y  + [ 0 + 3xy² - 4y²] - 10y² + x²y

= - x²y + 3xy² - 4y² -10y² + x²y                      Now combine like terms

=   (-x²y + x²y) + 3xy² + (-4y² - 10y²)

=       0 + 3xy² - 14y²

=  3xy² -  14y²       or    y²(3x - 14)